(untitled) (Tempo e Argumento, 2020)
This paper analyzes gender inequalities in the industrial development of Bahia, Brazil, on the basis of work-histories of women and men textile workers in Salvador, residents of a former workers’ villa owned by Fábrica São Braz, a factory which closed in the late 1950s. It compares and contrasts (dis)continuities found along gender and generation lines, showing that while most of these workers were not absorbed by new industry, this was especially true for the older generation and particularly marked in the case of women: 1) women worked at the less skilled occupations in the mill, many of which became obsolete with the production of synthetic textiles; 2) while traditional industries had relied primarily on the employment of women, new industry employed mainly men; and 3) jobs away from their neighborhood made the reconciling of wage work and domestic activities more difficult for women. They were left with few options but that of resorting to the so-called ‘informal sector’, becoming laundresses, domestic servants, petty-commodity producers, operators of food stands, and the like. This break with their condition as industrial workers would be extended to the succeeding generations of women in the community. The daughters of former factory workers are no longer factory workers themselves. These findings show that the divide resulting from the workings of patriarchal gender ideology has sharply imprinted the history of textile workers in Bahia. This calls for efforts towards the ‘gendering’ of Brazilian labor history. Keywords: Textile Workers. Gender Divide. Deskilling of Industrial Workers. Labor History. Bahia, Brazil.